International graduates on temporary post‐graduation visas in Australia: Employment experiences and outcomes. Issue 1 (11th August 2022) - Tran, Ly Thi; Tan, George; Bui, Huyen; Rahimi, Mark
Abstract: While a growing body of literature focuses on international students, their post‐study experiences and employment outcomes when they are on temporary graduate visas in the host country are under‐researched. The article addresses this critical gap by investigating international graduates' employment experiences and outcomes. It is derived from a study that includes 50 in‐depth interviews with employers, graduates and related stakeholders, and a survey with 1156 international graduates from 35 Australian universities . The study widens the lens of the discourse around international student graduates operating in a labour market which is overgeneralised by high‐skilled and low/unskilled segments. It shows that international graduates engage with a complex labour market which can see them work in or out of their professional disciplines in multiple forms of full‐time, part‐time, and casual jobs. In particular, the findings indicate that international graduates on post‐graduation visas who studied Information and Technology are more likely to secure employment in their field of study and spend less time to gain the first job in their area of expertise than those in Business and Engineering. This finding underscores the various effects of the structural conditions in different industries on international graduates' employability. The study also provides substantial insights into the increased vulnerability, deskilling, and precarity experienced by international graduates as migrant workers on temporary visas in the host country. It highlights a concern not only for the students, who place a premium on the acquisition of work experience, but also for host institutions and key destination countries and their delivery on promise in such a competitive international education market.